2009
DOI: 10.1016/j.visres.2007.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Attention during sequences of saccades along marked and memorized paths

Abstract: Natural scenes are explored by combinations of saccadic eye movements and shifts of attention. The mechanisms that coordinate attention and saccades during ordinary viewing are not well understood because studies linking saccades and attention have focused mainly on single saccades made in isolation. This study used an orientation discrimination task to examine attention during sequences of saccades made through an array of targets and distractors. Perceptual measures showed that attention was distributed alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 40 publications
1
60
0
Order By: Relevance
“…The manipulation of words to the left did not affect progressive eye movements, which remained at a typical saccade length of eight characters (Rayner, 1998). This result indicates that attention precedes movements of the eyes in whatever direction they are about to move and is supported by similar effects in scene perception (Gersch, Kowler, Schnitzer, & Dosher, 2009;Henderson et al, 1989).…”
Section: Discussionmentioning
confidence: 62%
“…The manipulation of words to the left did not affect progressive eye movements, which remained at a typical saccade length of eight characters (Rayner, 1998). This result indicates that attention precedes movements of the eyes in whatever direction they are about to move and is supported by similar effects in scene perception (Gersch, Kowler, Schnitzer, & Dosher, 2009;Henderson et al, 1989).…”
Section: Discussionmentioning
confidence: 62%
“…In these experiments, the saccade target and the perceptual target were both colored and the color of the perceptual target varied randomly, matching the saccade target's color on a subset of trials. We found that perceptual targets incidentally matching the color of the saccade target were slightly easier to discriminate than perceptual targets not matching the color of the saccade target (see also Gersch et al, 2008Gersch et al, , 2009. The effect of color congruency did not interact with the effect of spatial congruency, that is, the two effects were additive.…”
Section: Introductionmentioning
confidence: 67%
“…Additive effects when the two foci coincide are also conceivable. The possibility of multiple attentional foci has previously been discussed in studies in which sequences of eye movements or simultaneous eye and hand movements had to be performed (Baldauf & Deubel, 2008;Gersch et al, 2008Gersch et al, , 2009Godijn & Theeuwes, 2003;Jonikaitis & Deubel, 2011;Rolfs et al, 2010). In those studies, better discrimination has been observed at all movement goal locations in a sequence (not just the immediate saccade target; but see Gersch, Kowler, & Dosher, 2004), compared to locations that were never targeted by any movement.…”
Section: Discussionmentioning
confidence: 99%
“…The demand here is to make two or three saccades often as a response to a predetermined set of instructions (e.g., saccade to a target and then once more to the target two positions clockwise of it [17]; or execute two saccades when fixation is removed in response to a target which has stepped from location to another, [18, 19]). Alternatively sequences of saccades are made on the basis of a set of visual targets that are on screen at all times (box to box, to a set of green circles in amongst red ones, or directed by oriented Landolt C’s [20, 21, 22]) or ones that have been memorized such that subsequent saccades are memory-guided [21]. When considered across all of these studies, evidence consistently supports the position that information about saccade target locations beyond simply the next one is processed in parallel.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in performance in identification tasks have been found when targets (e.g., Gabor patches, [21]; letter identification [17]) are shown at future saccade target locations relative to other non-target locations. This has been interpreted as supporting a link between attentional enhancement at future saccade target locations and saccade programming such that attention is distributed in parallel along the sequence of saccade target locations.…”
Section: Introductionmentioning
confidence: 99%